2002
DOI: 10.1034/j.1398-9995.2002.13248.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of new IgE specificities to allergenic components in birch pollen extract during specific immunotherapy studied with immunoblotting and Pharmacia CAP System

Abstract: Sensitization to additional allergenic pollen components frequently occurs during prolonged birch RIT. However, the IgE levels are low and the clinical relevance is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 44 publications
3
109
0
1
Order By: Relevance
“…Another possibility is that important allergens are either not present in the allergen extracts in sufficient amounts or they exhibit poor immunogenicity [21,31]. Furthermore, it has been reported that administration of natural allergen extracts can induce new IgE specificities against allergens present in the extracts, which were not recognized by the patient before treatment [45][46][47].…”
Section: Factors Limiting the Broad Application Of Allergen-specific mentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that important allergens are either not present in the allergen extracts in sufficient amounts or they exhibit poor immunogenicity [21,31]. Furthermore, it has been reported that administration of natural allergen extracts can induce new IgE specificities against allergens present in the extracts, which were not recognized by the patient before treatment [45][46][47].…”
Section: Factors Limiting the Broad Application Of Allergen-specific mentioning
confidence: 99%
“…1, left, lower image), which will activate allergen-specific T cells to proliferate and release pro-inflammatory cytokines. Second, administration of allergens may induce allergen-specific IgE antibody production either by boosting of already existing B epsilon cells or by inducing de novo an allergenspecific IgE response [45][46][47]. The more the administered allergen resembles the structure of the natural allergen the more it will be able to boost already existing IgE responses and to exhibit sensitizing capacity.…”
Section: Factors Limiting the Broad Application Of Allergen-specific mentioning
confidence: 99%
“…[3][4][5][6][7] In our study only 5 patients had been treated with SIT more than 10 years before the first serum sample was obtained. We can therefore exclude SIT-induced effects on IgE reactivity profiles in our patients.…”
mentioning
confidence: 99%
“…Induction of IgE sensitization against native allergens instead of development of a protective immune response might be a major problem with current allergen extractbased vaccines [13]. In addition, some individuals might already be sensitized against some of the allergens in the vaccine content.…”
Section: Discussionmentioning
confidence: 99%